Epidemiology of tuberculosis in an urban slum of Dhaka City, Bangladesh. - Sayera Banu; Md Toufiq Rahman; Mohammad Khaja Mafij Uddin; Razia Khatun; Tahmeed Ahmed; Md Mojibur Rahman; Md Ashaque Husain; Frank van Leth (PLoS ONE, 2013)
Background The objectives of this study were to assess the tuberculosis (TB) burden and to provide an insight into the type of circulating M. tuberculosis species in urban slums of Bangladesh. We also aimed to test the feasibility of a larger transmission study in this setting. Methods This cross-sectional study was conducted in an urban slum of Dhaka city. The household members were actively screened to assess the presence of TB-related signs and symptoms; cough ≥ 3 weeks and body mass index (BMI) <17 kg/m(2). Sputum specimens from suspects were collected for acid fast bacilli (AFB) microscopy, culture and drug susceptibility testing. Genotyping of M. tuberculosis was done using spoligotyping and variable number tandem repeats of mycobacterial interspersed repetitive units typing. Results Among 9,877 adult screened for pulmonary TB (PTB), 25 were positive for AFB on microscopy and/or culture and the prevalence of new PTB cases was estimated to be 253/100,000. Only one child TB case was diagnosed among 5,147 child screened. Out of 26 cases, 21(81%) had cough for several duration and 5(19%) did not present with cough at the time of screening. One multidrug resistant case was found. Fifty two percent of all TB cases had BMI <17 kg/m2 (p = <0.001). Among the 20 analyzed isolates, 13 different spoligotype patterns were identified in which 5 clusters contained 12 strains and 8 strains had unique pattern. Conclusions The study revealed high prevalence of TB in urban slums. Screening using low BMI can be beneficial among risk group population. It is important to conduct larger study to validate clinical variables like cough <3 weeks and low BMI to define TB suspect and also to investigate the transmission of TB in slum settings.